Comparative analysis of phenotypic and genotypic detection of methicillin resistance among Staphylococcus aureus - Tulin Demir; Nilay Coplu; Berrin Esen (Wolters Kluwer Medknow Publications, 2016)
Aims: Staphylococcus aureus is a common pathogen causing a wide range of infections ranging from mild skin and soft tissue infections to severe, life-threatening infections. Accuracy in the detection of methicillin resistance is important to avoid treatment failures. The aim of this study was to compare the results of phenotypic and genotypic test methods to detect methicillin resistance and also to determine the antimicrobial susceptibilities. Materials and Methods: Two hundred and forty-two S. aureus strains isolated from skin and soft tissue samples were analyzed for methicillin resistance using oxacillin and cefoxitin disk diffusion (DD), oxacillin screen agar test, cefoxitin E-test, and mecA gene polymerase chain reaction (PCR). Results: 77 of 242 S. aureus isolates were mecA positive. Oxacillin, cefoxitin DD, oxacillin screen agar test and cefoxitin E-test exhibited sensitivities as 98.7%, 98.7%, 100%, 100%, and specificities as 96.9%, 97.5%, 96.9%, 97.5%, respectively. Conclusion: Results of oxacillin screen agar and cefoxitin DD test were in concordance with mecA gene PCR. Thus, it is determined that especially cefoxitin test can be an alternative to PCR in routine.